2021
DOI: 10.3390/catal11111286
|View full text |Cite
|
Sign up to set email alerts
|

Improved Brønsted to Lewis (B/L) Ratio of Co- and Mo-Impregnated ZSM-5 Catalysts for Palm Oil Conversion to Hydrocarbon-Rich Biofuels

Abstract: The purposes of this study are to investigate the effect of metal (Co and Mo) impregnation to ZSM-5 catalysts on the Brønsted to Lewis (B/L) ratio as the active sites of cracking reaction, and the catalysts’ performance testing for palm oil cracking to produce hydrocarbon-rich biofuels. Both metals were impregnated on the ZSM-5 catalyst using a wet-impregnation method. The catalysts were characterized using X-ray diffraction (XRD), X-ray Fluorescence (XRF), Scanning Electron Microscopy (SEM), Brunauer–Emmett–T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…As reported previously, the ionicity of reducible metal oxides could enhance the L acid sites due to the available orbitals of metal to receive the electrons. [27] It was confirmed by the XANES and XPS results that the majority of ionic reducible Re oxides was appear for the reduced NiRe 0.12 catalyst (See in Table 2 and Table 3). Therefore, it should be remarkably deduced that the addition of Re species into Ni species could boost the distribution of L acid sites.…”
Section: Nh 3 -Tpd and Pyridine-drifts Examinationsmentioning
confidence: 62%
“…As reported previously, the ionicity of reducible metal oxides could enhance the L acid sites due to the available orbitals of metal to receive the electrons. [27] It was confirmed by the XANES and XPS results that the majority of ionic reducible Re oxides was appear for the reduced NiRe 0.12 catalyst (See in Table 2 and Table 3). Therefore, it should be remarkably deduced that the addition of Re species into Ni species could boost the distribution of L acid sites.…”
Section: Nh 3 -Tpd and Pyridine-drifts Examinationsmentioning
confidence: 62%
“…According to Kianfar et al (2018), the use of ZSM-5/CaCO3 as a catalytic cracking catalyst improves the production of heavy hydrocarbons by 38.65%. Istadi et al (2021) also found that Ni-Co/HY catalyst supported cracking and deoxygenation mechanisms in the production of biofuels from palm oil reaching a yield of hydrocarbons and oxygenated by 98.46% and 1.54%, respectively. Meanwhile, cracking palm oil using a bifunctional Zn/ZSM-5 catalyst to produce hydrocarbon fuel and oxygen content by 71.78% and 4.07%, respectively, was reported by .…”
Section: Introductionmentioning
confidence: 80%
“…22 Recently, much research has focused on the ZSM-5-based catalyst in the HDO process. Riyanto et al 23 used Mo/ZSM-5 and Co/ZSM-5 catalysts with various Bro̷ nsted/Lewis acid center ratios to catalyze the HDO of palm oil. They observed that the biofuel yield was enhanced with the rising value of the Bro̷ nsted/Lewis acid center ratios.…”
Section: ■ Introductionmentioning
confidence: 99%